Clinicopathological study of renal biopsies - a two year study; - Angunawela, P.; Sheriff, M.H.R.; Fernando, H. (My University, 1992)
Five hundred consecutive renal biopsies were examined at the Department of pathology, Faculty of Medicine from January 1990 to November 1991. Two cores of renal tissue were obtained. One was fixed in 10% formal saline for immunohistochemical studies.The other was fixed in DBS solution for light microscopic studies. In a few selected cases 0.1 mm of renal tissue was fixed in 4% gluteraldehyde for electron microscopic studies. Haematoxyline and cosin H E) ,PAS and silver methanamine stains were performed on all biomine stains were performed on all biopsies.Immunohistochemistry was performed using IgG, IgM,IgA, antisera. One hundred and forty three had nephritic syndrome, 55 had features of nephritic/ nephritic syndrome, 26 had chronic renal failure and another 26 had acute renal failure. Seventeen transplant biopsies were included while 183 patients had persistant proteinuria or haematuria. Seventy four biopsies contained less than five glomeruli and were considered not sufficient four accurate diagnosis. Out of 426 biopsies 40% had minimal change, 13% had mesangial proliferation, 6% had mesangio- capillary glomerulonephritis, 0.5% had membranous glomerulonephritis, 8% had focal segmental glomerulosclerosis, 7.4 % had crescentic glomerulonephritis. 4.6% had extensive glomerulosclerosis, 10% were in the resolving stage of post-streptococcal glomeruhistological patterns like diabetic nephritis and pyelonephritis. Imminoohistochemical studies showed IgA immune complexes in 23 patients (5.6%). This study shows the histological patterns of glomerulonephritis in Sri lanka. This is the first time IgA nephropathy is documented in Sri Lanka